Infant feeding practices in first time mothers: a cross-sectional study - Hiranmayi, Anam; Ravanagomagan, M. G.; S., Jagadeeswari (International Journal of Research in Medical Sciences, 2025)
Background: Optimal infant nutrition during the early months of life is essential for growth, development, and disease prevention. Exclusive breastfeeding (EBF) is recommended for the first six months by World Health Organization (WHO) and United Nations Children's Fund (UNICEF). However, in many low- and middle-income countries, including India, actual breastfeeding practices are influenced by socio-cultural and economic factors, especially among first-time mothers. This study aimed to assess the knowledge, attitudes, and practices (KAP) regarding infant feeding among first-time mothers in an urban healthcare setting in India. Methods: A cross-sectional descriptive study was conducted between January and March 2025 at the Department of Pediatrics, Sree Balaji Medical College and Hospital, Chennai. A total of 383 first-time mothers with infants aged 0–6 months were selected using purposive sampling. Data were collected using a self-structured and pre-tested KAP questionnaire in English and Tamil. Descriptive and inferential statistics were used for analysis via statistical package for the social sciences (SPSS) version 21. Results: While 85% of participants were aware of the recommended duration for EBF, only 52.2% practiced it. Formula feeding was reported by 31.3%, and 15.7% had introduced animal milk before six months. Prelacteal feeding and bottle-feeding were practiced by 10.4% and 13.1%, respectively. Major barriers included perceived insufficient milk (31.3%), return to work (23.5%), and lack of support (20.9%). Health professionals (65%) were the primary source of breastfeeding information. Conclusions: Despite high awareness, a significant gap exists between knowledge and actual feeding practices among first-time mothers. Targeted educational interventions and support systems are essential to improve adherence to optimal infant feeding guidelines.